Modeling osmotic membrane processes without pressure and porosity simplifications - Chong, Y. K.; Liang, Y. Y. (Elsevier, 2025)
Accurate modeling of effective structural parameter and flux is critical to evaluating osmotic membrane performance. Most membrane processes favor computational efficiency by utilizing simplified approximation like neglecting the impact of pressure and assuming constant support layer porosity. This work introduces a comprehensive semi-empirical and computational model that eludes these typical simplifications for evaluating forward osmosis (FO), pressure assisted osmosis (PAO), pressure retarded osmosis (PRO) and osmotically assisted reverse osmosis (OARO). Our models (without neglecting pressure) demonstrate a more accurate prediction in effective structural parameters than the existing models as the existing models neglect the impact of pressure. This comprehensive semi-empirical model can simplify membrane evaluation in PAO, PRO, and OARO experiments by directly calculating the effective structural parameter from the results, eliminating the needs of FO test to pre-determine this parameter. This work also shows that assuming constant porosity can cause significant deviation in flux for a support layer with substantial variation in local porosity as this assumption causes the solute mass fraction within the support layer to deviate from its actual profile. Interestingly, constant porosity assumption is more reliable at higher transmembrane pressure to predict water flux because the transmembrane pressure dominates water flux over the effective osmotic pressure.